Drunken drive detection with smart ignition lock - S. L. A. Muthukarpan; M. N. Osman; M. Jusoh; T. Sabapathy; M. K. A. Rahim; M. Elshaikh; Z. I. A. Khalib (Bulletin of Electrical Engineering and Informatics, 2021)
Drink and drive issue have become solemnly that needs immediate attention. This is due to drivers’ ignorance towards road rules and regulations and their selfish attitude that caused loss of innocent lives. Although previously there is a drunk detecting mechanism using breathalyzer but it isn’t suitable for current fast-paced lifestyle. Therefore, to overcome these issues, this system is proposed. This system is fixed on vehicle’s steering to measure alcohol concentration reading using MQ-3 sensor from the driver’s exhaled breath. If the driver found to be drunk beyond the threshold level of 400 ppm, then ignition lock is activated and the car engine does not start till alcohol concentration falls to a safe level. Or, if the driver consumes an alcoholic drink while driving, upon exceeding permissible limit, the car slows down till it stops. Then, the location of the vehicle is tracked and sent as Google Map integrated link via text message to authorized unit. Simultaneously, the car buzzer goes off while the car slows down so that surrounding road users are aware of the driver’s condition and drives at a distance. The proposed detection system is highly potential to be implemented for reducing the drunk and drive accidents.